Teaching successful intelligence to gifted and talented students - Robert Sternberg; Elena Grigorenko; Mercedes Ferrando; Daniel Hernández; Carmen Ferrándiz; Rosario Bermejo (Revista Electrónica Interuniversitaria de Formación del Profesorado)
The aim of this study is to analyze the theory of successful intelligence as a strategy to meet the educational needs of gifted and talented students. First, we present the theory of successful intelligence as an alternative that allows for an in-depth study of the cognitive complexity of high ability from a broader perspective of intelligence. Second, we analyze the roles of students and teachers in the learning-teaching process. Third, we indicate some learning strategies aimed at promoting the management of resources in the classroom related to the analytical, synthetic or creative and practical intelligence. Finally, some conclusions are drawn.